PENGARUH SISA LEBIH PEMBIAYAAN ANGGARAN DAN BELANJA PEGAWAI TERHADAP BELANJA MODAL DI KABUPATEN GIANYAR TAHUN 2017-2018 - Ni Komang Kharisma Mia Mahartiningsih; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2020)
In improving public services, budget allocations must be more for the public interest like capitak expenditure. Sources of regional funding in creating regional infrastructure one of them is left over budget financing and employee spending. The aim of this research is to find out the influence remaining budget financing and employee expenditure towards capital expenditure. This research as conducted in the OPD in the Gianyar Regency with secondary data. Where the sample used is the same as the population. The study population and sample was 50.the theory used is agency theory. And the data used is secondarydata. From the research result obtained that the rest of the budget financing has not effect on capital expenditure and employee expenditure has a positive effect on capital expenditure.